Colourful cones: how did flower colour first evolve? - Rudall, Paula J (Journal of experimental botany, 2020)
Flowers with contrasting colours represent an iconic feature of Angiosperms. This review explores the cryptic clues that exist in both living and fossil seed plants for the evolutionary origins of flower colour. Abstract Angiosperms that are biotically pollinated typically produce flowers with bright and contrasting colours that help to attract pollinators and hence contribute to the reproductive success of the species. This colourful array contrasts with the much less multicoloured reproductive structures of the four living gymnosperm lineages, which are mostly wind pollinated, though cycads and Gnetales are predominantly pollinated by insects that feed on surface fluids from the pollination drops. This review examines the possible evolutionary pathways and cryptic clues for flower colour in both living and fossil seed plants. It investigates how the ancestral flowering plants could have overcome the inevitable trade-off that exists between attracting pollinators and minimizing herbivory, and explores the possible evolutionary and biological inferences from the colours that occur in some living gymnosperms. The red colours present in the seed-cone bracts of some living conifers result from accumulation of anthocyanin pigments; their likely primary function is to help protect the growing plant tissues under particular environmental conditions. Thus, the visual cue provided by colour in flower petals could have first evolved as a secondary effect, probably post-dating the evolution of bee colour vision but occurring before the subsequent functional accumulation of a range of different flower pigments.